From Campus to Business: The Impact of University Support, Subjective Norms, and Attitudes On Students Entrepreneurial Intentions - Setyawan, Andhy; Subali, Stefanus Budi Widjaja; Djayapranata, Grace Felicia (Journal of Entrepreneurship & Business, 2025)
Purpose: Entrepreneurship is one solution to overcome the problem of unemployment; therefore, this study aims to determine the factors that influence entrepreneurial intentions Method: This study using 208 data respondents. Collecting data through online survey with judgmental sampling. The data analyzed with SEM Methods. Result: Based on this findings, perceived university support plays important role to boost the subjective norm and positive attitude towards entrepreneurship. The subjective norm and positive attitude had effect on forming entrepreneurial intention. This result has effect on management decision making.